Characterization of Wild Blueberry Polyphenols Bioavailability and Kinetic Profile in Plasma over 24‐h Period in Human Subjects - Zhong, Siqiong; Sandhu, Amandeep; Edirisinghe, Indika; Burton‐Freeman, Britt (Molecular nutrition & food research, 2017)
Scope Understanding the metabolic fate of polyphenols from plant foods can aid in developing dietary recommendations that maximize their health benefits. Wild blueberries (WBB) provide a distinctive composition of dietary anthocyanins and chlorogenic acid (CGA). Methods and results This is a single blind, randomized, two‐arm crossover controlled study. Human subjects ingested a WBB beverage (25 g freeze dried WBB powder) or placebo beverage with a meal and plasma was collected over 24 h. Anthocyanins, CGA and their metabolites were characterized and quantified in beverages and in plasma using targeted and non‐targeted mass analyses. Bioavailability of WBB anthocyanins and 3‐CGA was 1.1 and 0.2%, respectively. Parent anthocyanins and 3‐CGA peaked ≈2 h post ingestion, while phase II metabolites, including glucuronide conjugates of peonidin, delphinidin, cyanidin and petunidin peaked ≈ 2.6, 6.3, 7 and 8.8 h, respectively. Phenolic acids (metabolites) peaked between 0.5 and 24 h. Biphasic responses were evident suggesting preferential enterohepatic recycling for some compounds. Conclusion The data indicate bioavailability of early and late phase WBB metabolites peaking at different times during the 24 h period, which may be important for maximizing their biological activity. Anthocyanins, chlorogenic acids and their metabolites are quantified in human plasma over 24 h after oral ingestion of wild blueberries. Parent compounds and an array of metabolites appeared and peaked in plasma between 15 min and 8 h with one metabolite, hippuric acid, continuing to increase at 24 h. Bi‐phasic metabolite responses may be indicative of enterohepatic circulation. Characterizing absorption and clearance patterns, including major metabolites formed can guide study design development testing biological activity during changing physiological status over 24 h.